Small Scale Enterprises and Unemployment Challenges in Ogun State Nigeria - Adurayemi, Adu Cecilia; Christopher, Wiiliams Adekunle (MultiTech Publisher, 2024)
This research examined the effect of micro-scale enterprises on employment in Ogun State. The primary source of data was used through the administration of one hundred copies of the questionnaire. A simple regression analysis was used from which it was found that the small-scale enterprises have reduced the unemployment rate in Ogun State thus reducing the crime rate and enhancing the income level of owners. It was recommended that the government should fund small-scale enterprises through the Bank of Industry and provision of social amenities where needed.